2008
DOI: 10.1002/pssa.200824040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the milling conditions on the formation of nanostructured Fe–Co powders

Abstract: Nanostructured Fe–12Co (wt%) powders were prepared by mechanical alloying in a planetary ball mill. The milling process was carried out at different milling conditions. The obtained powders were characterized by X‐ray diffraction, 57Fe Mössbauer spectrometry and magnetic measurements. The low and high speed ball‐milling conditions lead to the formation of a single and two‐bcc Fe(Co) structure, respectively, having different crystallite sizes, microstrains hyperfine parameters and magnetic properties. The avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Bolokang also suggested that distortion could be one of the causes of increase in lattice parameter [6]. In case of smaller crystallites (i.e., *11 nm), which favor higher solubility of vacancies, lattice distortions are more significant and are reported for many systems obtained by BM [25,26]. This result is quite inconsistent with Sen et al [9], which is due to the omission of lattice distortion.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 51%
“…Bolokang also suggested that distortion could be one of the causes of increase in lattice parameter [6]. In case of smaller crystallites (i.e., *11 nm), which favor higher solubility of vacancies, lattice distortions are more significant and are reported for many systems obtained by BM [25,26]. This result is quite inconsistent with Sen et al [9], which is due to the omission of lattice distortion.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 51%
“…This is due to the allotropic transformation of Co from the fcc to the hcp structure. The allotropic phase transformation of cobalt processed by ball milling was reported by many authors [15][16][17][18][19][20]. At ambient temperature, the fcc-Co is a metastable phase which can be transformed into the hcp structure by mechanical milling.…”
Section: Structural Studymentioning
confidence: 90%
“…The present work is devoted to the study of the formation of the ball-milled Cr 20 Co 80 using scanning electron microscopy (SEM) and X-ray diffraction (XRD). This analysis focuses on the relationship between microstructural parameters and phase transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Among the non-equilibrium processing techniques that are used for the synthesis of NC materials, mechanical alloying (MA) has received serious attention because of the versatility and the favorable economics of the process. [12][13][14] During mechanical alloying, powders undergo a severe plastic deformation, which introduces a number of defects (dislocations, grain boundaries, vacancies, and interstitials) into the material. The constituents that favor the formation of a metastable structure can then ''self assemble'' into nanoscale grains.…”
Section: Nanocrystalline (Nc) Fe-al Intermetallicmentioning
confidence: 99%